Vitamin K and oxidative phosphorylation - Horth, C. E. (1966)
1. Oxidative phosphorylation was studied in a cell-free preparation of Mycobacterium phlei and in rat-liver mitochondria. Phosphorylation was destroyed in both systems by long-wave ultraviolet radiation and restored by the addition of small amounts of [2-Me-(14)C,(3)H]phylloquinone. When the radioactive quinones were recovered from the phosphorylating system and chromatographed with carrier phylloquinone and menaquinone-4 in adsorption and partition systems, only the phylloquinone band was labelled, and its isotopic ratio was identical with that of the original [2-Me-(14)C,(3)H]phylloquinone. This result does not support the contention that the role of vitamin K in oxidative phosphorylation involves a cyclic mechanism with intermediate formation of a quinone methide. 2. When the [2-Me-(14)C,(3)H]phylloquinone was given intravenously to rats and radioactive phylloquinone isolated from their liver mitochondria and microsomes 20hr. later, its isotopic ratio was unchanged. There was thus no evidence for quinone methide formation in vivo. No measurable conversion of phylloquinone into menaquinone-4 was observed. 3. When [(14)C]menadione was given intraperitoneally to rats whose alimentary tract had been treated with neomycin, conversion into menaquinone-4 was found in the liver mitochondria and microsomes, but there was also some indication that there had been synthesis of phylloquinone.